Identification of Degradation Areas of Ecological Environment and Degradation Intensity Assessment in the Yellow River Basin - Li, Tiantian; Zhang, Qiang; Singh, Vijay P.; Zhao, Jiaqi; Song, Jinbo; Sun, Shuai; Wang, Gang; Shen, Zexi; Wu, Wenhuan (Frontiers in Earth Science, 2022)
Ecological conservation and high-quality development of the YRB (Yellow River Basin) has been adopted as a national strategy. However, the ecological environment of the YRB is fragile and it has degraded in recent years. Here we proposed an ecological degradation index system based on the Pressure-State-Response (PSR) model and evaluated trends in ecological degradation of the YRB using the Mann-Kendall trend test. We found an upward-downward-upward trend in the ecological degradation index (EDI) during the period of 2000 to 2019. We also observed an intensifying degradation of eco-environment from the upper to the lower YRB. Meanwhile, 69.9% of the YRB is under degraded eco-environment, while 29.5% of the YRB is dominated by improved eco-environment. Specifically, the ecological degradation intensity of Henan and Shandong Province with dense population and rapid economic development is the highest. Due to active and effective improvement measures taken by the government, the degradation intensity has been having a decreasing tendency. However, higher degradation intensity of eco-environment of the YRB should arouse human concerns. As to the driving factors, human activities can be regarded as the major driving factors for degraded eco-environment, and water stress and economic development exert increasing impacts on the eco-environment of the YRB. Our finding can provide a decision-making basis for the ecological management and high-quality development of the YRB.